Production as Origen of Surplus-Value in Marxist Theory - Boundi Chraki, Fahd (Universidad Pedagógica y Tecnológica de Colombia, 2017)
The aim of this research is: 1) clarify the main source of profit, i.e., the surplus value, derives from the sphere of production; 2) show that the necessary and sufficient condition for sustaining capitalist society is that betweencapital and labor has to mediate a relationship based on the exploitation of the labor force. Firstly, Marx’s theory will be confronted with the marginalist approach. Secondly, the secret of surplus-value is decrypted as the sale of labor force, showing in this way the dual character of Marxian system calculation. Finally, through the fundamental Marxian theorem it will be verified the hypothesis on the exploitation of the labor force as necessary and sufficient condition to obtain positive earnings.